2011
DOI: 10.1016/j.jacc.2010.11.022
|View full text |Cite
|
Sign up to set email alerts
|

The Primary Benefits of Angiotensin-Converting Enzyme Inhibition on Cardiac Remodeling Occur During Sleep Time in Murine Pressure Overload Hypertrophy

Abstract: The ACE inhibitor captopril benefited cardiovascular remodeling only when administered during sleep; wake-time captopril ACE inhibition was identical to that of placebo. These studies support the hypothesis that the heart (and vessels) remodel during sleep time and also illustrate the importance of diurnal timing for some cardiovascular therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 30 publications
(31 reference statements)
2
48
0
1
Order By: Relevance
“…In 1 recent human study a 5 mm Hg reduction in sleep-time systolic BP caused a 17% reduction in adverse cardiovascular events in a hypertensive population, 96 and, in hypertensive mice, captopril prevented cardiovascular remodeling only when administered before sleep. 97 …”
Section: Hypertensionmentioning
confidence: 99%
“…In 1 recent human study a 5 mm Hg reduction in sleep-time systolic BP caused a 17% reduction in adverse cardiovascular events in a hypertensive population, 96 and, in hypertensive mice, captopril prevented cardiovascular remodeling only when administered before sleep. 97 …”
Section: Hypertensionmentioning
confidence: 99%
“…Indeed, several clinical studies have discovered that nighttime angiotensinconverting enzyme inhibitor achieves better BP control and is associated with lower risk for total cardiovascular disease events (15)(16)(17)(18). Furthermore, study in mice showed that rest-time angiotensin-converting enzyme inhibitor results in improved cardiac remodeling even when controlled for BP (19). Additional therapy aimed at facilitating the resynchronization using both behavioral (e.g., feeding, exercise, lighting conditions) and pharmacological modifications (melatonin) may be effective.…”
Section: Inflammationmentioning
confidence: 99%
“…In this model, a 10-h/10-h light-dark cycle was used to disrupt the circadian clock in mice, which led to increased cardiac hypertrophy and reduced contractility compared with mice on a normal 12-h/ 12-h light-dark cycle (86). Furthermore, in this same model, it was shown that nonblood pressure-dependent antihypertrophic benefits of the angiotensin-converting enzyme (ACE) inhibitor captopril were increased more during the inactive phase than the active phase (87). Interestingly, using the same model, it was demonstrated that multiple genes involved in cardiac remodeling, glycolysis, and fatty acid metabolism were significantly altered.…”
Section: Cardiovascular System and The Kidneymentioning
confidence: 99%